Intercarrier interference cancellation based on iterative detection algorithm for OFDM systems over time-varying channels - WANG Xia; ZHU Shi-hua (Tongxin xuebao)
In order to effectically cancel the intercarrier interference（ICI） in the OFDM（orthogonal frequency-division multiplexing） systems,a novel iterative detection algorithm was proposed based on parallel interference cancellation.With the principle of maximize the minimum signal-to-interference and noise power ratio,the received signal was proc-essed by decision,reconstruction and ICI cancellation,iterative algorithm based on ICI cancellation was set up,the flow chart on signal detection was given.On the basis of analysis on time-varying channel,the influence of the normalized Doppler frequency offset on the system performance was investigated.Computer simulation results were presented.Simulation results show that the proposed scheme can improve the system performance significantly by using of the time diversity of time varying channel.The computational complexity can be reduced form O（N 3） toO（N）.